Re: Idempotence
- To: mathgroup at smc.vnet.net
- Subject: [mg37830] Re: Idempotence
- From: "Steve Luttrell" <luttrell at _removemefirst_westmal.demon.co.uk>
- Date: Thu, 14 Nov 2002 06:11:43 -0500 (EST)
- Sender: owner-wri-mathgroup at wolfram.com
Duh! Of course it should have been (list2 // Expand) /. {a^2 -> a, b^2 -> b, c^2 -> c}. Steve Luttrell "News Admin" <news at news.demon.net> wrote in message news:aqqdt1$sfp$1 at smc.vnet.net... > You can reduce list2 by expanding everything out, then implementing > idempotence using replacement rules. In this case all you need are the rules > {a^2 -> 1, b^2 -> 1, c^2 -> 1}, but more generally you would need rules to > deal with higher powers as well. > > (list2 // Expand) /. {a^2 -> 1, b^2 -> 1, c^2 -> 1} > > yields the result > > {-3 + 4 b + 4 a c - 4 a b c, c, 1} > > This isn't the same as list1 so I presume there was a typo in your question. > > > Steve Luttrell > > "Tilo Schröder" <tilo.schroeder at unibw-muenchen.de> wrote in message > news:aqo05b$fpa$1 at smc.vnet.net... > > Hello, > > > > I'm quite new in operating with Mathematica. Solving a problem concerning > > network reliability I have to implement an algorithm which uses > idempotence > > (e.g.: a*a=a, a^2*b^3=ab). > > As a result of this fact, the following lists should be the same: > > > > list1={b+a c-a b c,c,1} > > list2={2 b+2 a c-a b c-a c (b+a c-a b c)-b (b+2 a c-a b c-a c (b+a c-a b > > c)),c,1} > > > > The result of "list1===list2" should be true. > > > > Does anybody have a hint or an idea how to solve it with Mathematica? I > > couldn't find anything about it even on Wolfram's webpage. > > > > Thank you in advance. > > > > Tilo. > > > > > > > > >